Towards historicizing "magic" in antiquity - Otto, Bernd-Christian (Numen, 2013)
Even though the concept of "magic" has suffered severe criticism in academic discourse, the category continues to be used in many disciplines. During the last two decades, classicists in particular have engaged in a lively discussion over "magic" and have produced an impressive amount of written output. Given the impossibility of defining "magic" in a consistent and widely accepted manner, one cannot help but wonder what these scholars are actually talking about. Hence this paper purports (a) to critically review the recent debate on "magic" in Classical Studies, (b) to advocate for abandoning an abstract category of "magic" in favour of a proper analysis of ancient sources and (c) to historicize the term "magic" in Antiquity, that is, to muse on its ancient semantics, functions, and contexts. This methodological approach does not only overcome the major problems inherent in modern definitions of "magic," but will also yield new insights into terminologies, modes of thought and speech strategies that underlie ancient religious discourses. © 2013 Koninklijke Brill NV, Leiden, The Netherlands.
Created from Fastlane, Scopus look-up
Keywords: Classical Antiquity; Classical Studies; Conceptual history; Magic; Religious Studies